2011
DOI: 10.1007/s10722-011-9661-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of cultivated and wild Ussurian Pear (Pyrus ussuriensis Maxim.) in China evaluated with M13-tailed SSR markers

Abstract: Eight genomic SSR markers with a M13 tail attached were used to assess the genetic diversity of 72 Ussurian Pear accessions (Pyrus ussuriensis Maxim.) in China. The M13-tailed method was effective in discriminating all the 32 wild accessions. All the 40 Ussurian Pear cultivars could be successfully discriminated with the exception of 4 sets of synonymies or spots. A total of 108 alleles were obtained with an average of 13.5 per locus. The expected heterozygosity, observed heterozygosity, and power of discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In this study, the average value of heterozygosity and an average number of effective allele were 0.61 and 14.3 in 109 accessions by the nine SSR same as our previous study. In this study, observed heterozygosities (H o ) for individual loci with an average value of 0.61, which is comparable with a value of 0.63 (Kimura et al 2002;Bao et al 2007;Cao et al 2011a). However, this value is much higher than the values of 0.50 for 58 Iwate accessions (Katayama et al 2007), 0.48 for 114 European and Asian pears (Bassil and Postman 2010), 0.44 for 63 European pear accessions (Wünsch and Hormaza 2007).…”
Section: Discussionsupporting
confidence: 78%
“…In this study, the average value of heterozygosity and an average number of effective allele were 0.61 and 14.3 in 109 accessions by the nine SSR same as our previous study. In this study, observed heterozygosities (H o ) for individual loci with an average value of 0.61, which is comparable with a value of 0.63 (Kimura et al 2002;Bao et al 2007;Cao et al 2011a). However, this value is much higher than the values of 0.50 for 58 Iwate accessions (Katayama et al 2007), 0.48 for 114 European and Asian pears (Bassil and Postman 2010), 0.44 for 63 European pear accessions (Wünsch and Hormaza 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Terzopoulos and Bebeli (2008) suggested that using only morphological/agronomic traits is not adequate for the development of gene pools since either these traits are influenced by environmental factors and stage of plant development or they reveal only limited variation. The rapid development of molecular markers has provided new tools for evaluating germplasm and assessing the genetic diversity and population structure of plant species (Baranski et al 2012;Boczkowska et al 2012;Cao et al 2012;Mir et al 2012;Roy et al 2012;Sardos et al 2012;Wang and Li 2012). Different types of markers such as isozymes, random amplification of polymorphic DNAs (RAPDs), restriction fragment length polymorphisms (RFLPs), target region amplification polymorphisms (TRAPs), sequence-specific amplification polymorphisms (SSAPs), and amplified fragment length polymorphisms (AFLPs) have already been used for the assessment of genetic variability and diversity and to perform fingerprinting of Vicia species and V. faba L. accessions (Van de Ven et al 1990;Przybylska et al 1998;Gresta et al 2010;Kwon et al 2010;Liu and Hou 2010;Ouji et al 2012;Waly et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their reproducibility, multi-allelic nature, co-dominant inheritance, relative abundance, and good genome coverage (Powell et al, 1996), SSR markers have been largely applied to genetic diversity studies (Gupta and Varshney, 2000;Chen et al, 2011;Zhang et al, 2013) and used in a variety of applications related to pears, demonstrating their adaptability for Pyrus (Yamamoto et al, 2002;Bao et al, 2007;Katayama et al, 2007;Yao et al, 2010;Cao et al, 2012). SSR loci consist of randomly repeated DNA regions with motif lengths of one to six base pairs (bp) and are spread throughout the genome (Tóth et al, 2000).…”
Section: Introductionmentioning
confidence: 99%